DNA taxonomy confirms the identity of the widely-disjunct mediterranean and atlantic populations of the tufted ghost crab ocypode cursor (Crustacea: Decapoda: Ocypodidae) - Vecchioni, L.; Marrone, Federico; Deidun, Alan; Adépo-Gourène, Béatrice A.; Froglia, Carlo; Sciberras, Arnold; Bariche, Michel (Zoological Society of Japan zsocj@al.rimnet.ne.jp, 2019)
The distribution area of the tufted ghost crab Ocypode cursor includes two widely separate sub-areas, i.e. the tropical and subtropical Atlantic coasts of Africa and Macaronesia, and the central-eastern Mediterranean basin. The current disjunct distribution of the species is possibly the remnant of a previous wider and continuous distribution area that was fragmented during the Pleistocene, with the disappearance of the species from the temperate Atlantic Ocean and the western Mediterranean basin, and its survival in the warmer areas of the eastern Atlantic and the Mediterranean Sea. Such disjunction is thus compatible with an ancient isolation between the Mediterranean and Atlantic populations of the species, which could in fact constitute two well-characterized independent evolutionary lineages, or even two cryptic species. Unexpectedly, the sequencing of a fragment of the mtDNA COI gene from Mediterranean and Atlantic Ocypode cursor allopatric populations showed the cohesion of the species throughout its distribution range, and the nesting of Mediterranean populations within the single Atlantic population studied. This pattern is hereby tentatively ascribed to an incomplete lineage sorting due to the large population sizes of both the Atlantic and Mediterranean subpopulations of the species. The current westward expansion of the species in the Mediterranean Sea originating from the Levantine basin, due to ongoing regional sea warming, follows a typical phalanx dispersal mode. © 2019 Zoological Society of Japan
Keywords: Allopatric populations; Disjunct distribution; Phalanx dispersal mode; Sea warming; Tufted ghost crab